Generic Model for Multi-Phase Ring Oscillators - Pereira, Paula C. (2019)
This work was supported by national funds through FCT, Fundacao para a Ciencia e a Tecnologia, under project UID/CEC/50021/2013 and project UNSEEN 02/SAICT/2017.